Profil Mikrobiologis Pollard yang Difermentasi dengan Ekstrak Limbah Pasar Sayur pada Lama Peram yang Berbeda - Cahya Setya Utama; Bambang Sulistiyanto; Bhakti Etza Setiani (Jurnal Agripet, 2013)
Profile microbiological of pollard fermented with extract of waste vegetable market in different long ripenedABSTRACT. The purpose of fermentation is to produce a product (material feed) that have nutritional content, texture and better biological availability, while it also can reduce the anti-nutritional. Microorganisms are often used as probiotics in feed is kind of Lactobacillus sp and Saccharomyces cerevisiae. Microorganisms are able to produce secondary metabolites such as -glucan, mannan oligosaccharides and anti-cancer. Very familier as probiotic Lactobacillus among humans or livestock , while saccharomyces cerevisiae have specific characteristics in animal feed because of its ability to produce glutamic acid which can increase feed palatability. Grant Saccharomyces cerevisie can enhance digest protein and fiber, such as cellulose and hemicellulose , with Sacaromyces cerevisiea supplementation can increase the rate of short-chain fatty acids in cecum and suppresses the growth of bacteria from the Enterobacteriaceae species. Observing the above, needed an activity to find additional engineering efforts antibiotics as a source of natural probiotic , prebiotic and synbiotic on the particular poultry and livestock in general, to take advantage of the waste as a probiotic supplement that naturally produced feed additives to support healthy organic livestock production and economically.